Utilization of Facebook Social Media as a Popular Communication Media in 2025 - A Endang Maulana; A Harsada (Brilliant International Journal Of Management And Tourism, 2025)
The purpose of this research is to examine in depth how Facebook social media can be utilized as a popular communication medium towards 2025. Through a review of various sources and previous studies, this research aims to understand the trends and developments in the use of Facebook as a primary communication tool in the future. The research method uses a qualitative approach with a literature study and in-depth interviews. Three informants who were considered knowledgeable in the area were interviewed to gather the necessary data. The results indicate that Facebook remains the dominant social media platform and continues to grow as a communication medium that facilitates interaction and socialization among various groups. Furthermore, the platform’s use is expected to increase the effectiveness of digital communication, support a variety of social and economic activities, and strengthen interpersonal connections in the virtual world. Facebook’s role as a central communication tool is predicted to be pivotal in shaping the future of digital communication and social interactions.